2019
DOI: 10.18203/2320-1770.ijrcog20194886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk factors for surgical site infection following caesarean section

Abstract: Background: Assessment of surgical site infection is an important factor to determine the functioning of the health care system. Objectives of this study was to estimate the incidence of surgical site infection among caesarean section cases and to determine the risk factors associated with surgical site infection and comparison with patients having healthy wounds.Methods: One thousand pregnant women who underwent caesarean section were divided into two groups: Group 1 (cases): Those who had SSI within 30 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Our study found that the younger (aged <25 years) are at high risk of developing SSI after CS. In India, inconsistent results are found in the literature in this regard [10,14,20,26]. We found higher risk with emergency CS with borderline significance; but most studies in literature have confirmed a higher risk of SSI with emergency CS [16,27,28].…”
Section: Discussioncontrasting
confidence: 59%
“…Our study found that the younger (aged <25 years) are at high risk of developing SSI after CS. In India, inconsistent results are found in the literature in this regard [10,14,20,26]. We found higher risk with emergency CS with borderline significance; but most studies in literature have confirmed a higher risk of SSI with emergency CS [16,27,28].…”
Section: Discussioncontrasting
confidence: 59%
“…In India, inconsistent results are found in the literature in this regard. [10,14,20,26] We found higher risk with emergency CS with borderline significance; but most studies in literature have confirmed a higher risk of SSI with emergency CS. [16,27,28] In the present study, Staphylococcus aureus, a gram-positive organism, was the commonest organism isolated from caesarean wound infections.…”
Section: Discussionmentioning
confidence: 50%